2022
DOI: 10.1029/2022ms003206
|View full text |Cite
|
Sign up to set email alerts
|

Convective Momentum Transport and Its Impact on the Madden‐Julian Oscillation in E3SM‐MMF

Abstract: Convective momentum transport (CMT) is the process of vertical redistribution of horizontal momentum by small‐scale turbulent flows from moist convection. Traditional general circulation models (GCMs) and their multiscale modeling framework (MMF) versions poorly represent CMT due to insufficient information of subgrid‐scale flows at each GCM grid. Here the explicit scalar momentum transport (ESMT) scheme for representing CMT is implemented in the Energy Exascale Earth System Model‐Multiscale Modeling Framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…This wet bias over the northwestern tropical Pacific is largely removed with the use of a 3D CRM domain (Figures S1d and S1e in Supporting Information ), consistent with the result of Yang et al. (2022). They also suggested that 3D produced a weaker MJO compared to the 2D case, which can be partly attributed to the different structure of background zonal flow.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This wet bias over the northwestern tropical Pacific is largely removed with the use of a 3D CRM domain (Figures S1d and S1e in Supporting Information ), consistent with the result of Yang et al. (2022). They also suggested that 3D produced a weaker MJO compared to the 2D case, which can be partly attributed to the different structure of background zonal flow.…”
Section: Resultssupporting
confidence: 88%
“…The difference in precipitation between 2D and 3D is consistent with the findings of Yang et al. (2022), who also suggested that 3D produced a weaker MJO than 2D, partly due to difference in the zonal flow. However, in comparison to the striking effect of dimensionality, impacts of CMT are minor in reducing this precipitation bias.…”
Section: Concluding Discussionsupporting
confidence: 91%
“…(2021b) found that the role of radiative feedbacks in TC genesis diminished with surface warming. Therefore, both TCs and the MJO can emerge without radiative feedbacks, as demonstrated by studies using CRMs (Muller & Romps, 2018; Reyes & Yang, 2020; Wing et al., 2016), as well as high‐resolution GCMs (Hsieh et al., 2023; Zhang et al., 2021b) and super‐parameterized GCMs (Arnold & Randall, 2015; Yang & Hannah, 2022). In this study, we show that CSA can emerge under similar conditions, suggesting that the underlying physics of the three distinct phenomena may share a common foundation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A detailed discussion of the LMSE analysis and its comparison to the conventional column MSE analysis can be found in Yao et al (2022). The framework has also been applied to study TCs and the MJO recently (Yang & Hannah, 2022;Zhang et al, 2022).…”
Section: The Vertically Resolved Mse Variance Frameworkmentioning
confidence: 99%
See 1 more Smart Citation